A Trend Analysis of Project-based Learning in Chemistry Experiment: A Bibliometric Analysis - Ika Hasanah; Sjaeful Anwar; Iqbal Musthapa (Jurnal Penelitian Pendidikan IPA, 2024)
Project-based learning is a global trend, widely adopted across countries. Project-based learning has developed diversely by emphasizing interdisciplinary, cross-domain, and regional collaboration. To provide in-depth resources for researchers and educators on project-based learning in chemistry experiments, this study aims to make a bibliometric analysis on the topic of project-based learning globally using publication characteristics analysis. The database used in this study used Scopus and obtained 5900 articles from 2018-2023. Bibliometric analysis was analyzed using VOSviewer and Microsoft Excel. The results of the bibliometric analysis show that Boone, C.D. is the author with the highest number of citations on the research topic, Project-based learning in a chemistry experiment. The United States is the most productive country in researching this topic, with 1351 articles. The most influential journal with the highest number of articles is the Journal of Physics Conference Series, with 243 articles. The major contextualized learning literatures in this study tend to fall into broad groups such as Project-based Learning, Education, and STEM Education. These findings suggest the need for multidisciplinary and cross-disciplinary studies on project-based learning research on chemistry learning and advocate for the inclusion of project-based learning research in education from a broader geographical context.